2011
DOI: 10.1007/s11010-011-0949-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of polyamines in determining the cellular response to chemotherapeutic agents: modulation of protein kinase CK2 expression and activity

Abstract: Numerous studies have shown that platinum compounds stimulate the expression of the polyamine catabolic enzyme spermidine/spermine N(1)-acetyltransferase resulting in anti-proliferative activity and apoptosis. As many cancer cell types including pancreatic cancer cells express high levels of polyamines, the possibility to develop anti-tumor strategies to deplete polyamine pools has drawn considerable attention in recent years. This has been effectively accomplished by treating cells with platinum drugs in comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Spermidine is a polybasic compound that reacts with an acidic cluster of CK2β to activate the CK2 holoenzyme ( 37 ). Notably, we found that long-term exposure to 3 mM spermidine ingested via drinking water activates CK2, restores senescence, and ameliorates premature aging phenotypes in Zmpste24 −/− mice without inducing any tumors in the examination period in mutant or WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…Spermidine is a polybasic compound that reacts with an acidic cluster of CK2β to activate the CK2 holoenzyme ( 37 ). Notably, we found that long-term exposure to 3 mM spermidine ingested via drinking water activates CK2, restores senescence, and ameliorates premature aging phenotypes in Zmpste24 −/− mice without inducing any tumors in the examination period in mutant or WT mice.…”
Section: Discussionmentioning
confidence: 99%